The Role of the Public Library in Developing Canadians’ Information Literacy Skills - Julien, Heidi; Breu, Reegan (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper reports on a national survey of information literacy (IL) instruction in urban and rural public libraries, and public librarians’ attitudes towards these services. The survey is the first phase of a study exploring the actual and potential role of Canadian public libraries in developing the public’s IL skills. Cette étude présente un sondage national sur les programmes de connaissances informationnelles (CI) dans les bibliothèques publiques urbaines et rurales et les attitudes des bibliothécaires envers ces services. Le sondage constitue la première étape d’une étude exploratoire sur le rôle réel et potentiel des bibliothèques publiques canadiennes dans le développement des connaissances informationnelles (CI) du public.